EFFECTS OF A REVERSE OSMOSIS-WATER TREATMENT PLANT BRINY CONCENTRATE DISCHARGED INTO AN ESTUARY. - Kleber, Katharine E. (East Carolina University, 2010)
Reverse Osmosis Water Treatment Plants (RO-WTPs) create potable water and a briny concentrate that must be disposed; often it is discharged into nearby surface waters. Currently, there is no published research to examine effects of this discharge on the ambient environment or on resident and transient biota. One established RO-WTP discharge location was used as a model and compared with a control location within the same embayment and the locations of two RO-WTPs pre-construction. These two plants may discharge up to eight times more concentrate into the estuary. A one-year study used acoustic Doppler current profilers; Hydrolab sondes; a YSI meter; and biological and water collections to profile each location. Water movements at all locations were correlated with wind velocity measured at the USCG-EC weather station and the tide cycle at Mann's Harbor marina. Average velocity was lowest at the established RO-WTP and highest at the two proposed locations in fall 2005. Salinity varied significantly (p < 0.001) between the established RO-WTP and one of the proposed locations. From the four locations, we collected 21 species of macroinvertebrates. Location and date were not found to be significant. The effect of briny discharge on two species of macroinvertebrates dissipated beyond 5 m of the diffuser. The macrozooplankton (13 taxa) showed significant differences by date but not location while for the nekton (35 species) showed significant temporal differences (Spearman's Rho = 0.669) and moderate differences by location (Spearman's Rho = 0.237). There was no evidence that the RO-WTP has a significant impact on either the macrozooplankton or nekton collected. Overall, the biotic communities sampled from the four locations are typical for oligohaline to mesohaline estuaries. There were no significant differences in diversity for any biota collected. It is recommended that 1) data collection related to the discharge continue; 2) measurable indicators of biotic integrity from oligohaline to mesohaline environments be developed; and 3) post-construction samples at the two proposed RO-WTPs continue so as to investigate the effects of increased volume of brine on the local surface water as well as the resident and transient biota.
EFFECTS OF A REVERSE OSMOSIS-WATER TREATMENT PLANT BRINY CONCENTRATE DISCHARGED INTO AN OLIGOHALINE ESTUARY.
Keywords: Biology; Water resources management; Saline water conversion plants--Waste disposal--North Carolina; Saline water conversion--Reverse osmosis process--North Carolina; Water--Purification--Reverse osmosis process--North Carolina; Marine invertebrates--Effect of water quality on--North Carolina--Albemarle Sound; Marine zooplankton--Effect of water quality on--North Carolina--Albemarle Sound; Nekton--Effect of water quality on--North Carolina--Albemarle Sound